Psychoeducation on Relationship Uncertainty for Digital Communities: Psikoedukasi Ketidakpastian Relasi Komunitas Digital - Yusainy*, Cleoputri; Rachmayani, Dita; Hapsari, Farhana Ilmaya; Khairanti, Nabila (Universitas Lancang Kuning, 2024)
The advancement of digital technology has brought about a change in the pattern of interpersonal relationshipsamong youth. Uncertainty in relationships can cause distress to individuals involved and impact their mental health. The community service activity was conducted in partnership with the Manusiabiasa digital community with the goal of offering psychoeducation on emotional regulation strategies in dealing with relational uncertainty. The program began with an opinion poll among Instagram followerof the partners(N = 154; Mage= 20.7 years, SD = 6.78; 79.9% female) to uncover different terms that describe relational uncertainty. Psychoeducationparticipants (N = 173; Mage= 22.6 years, SD = 4.45; 87.7% female) reported increases in positive feelings and decreases in negative feelings. The results of this psychoeducation found that most participants were able to choose adaptive regulatory strategies (mindfulness = 31.3%) and cognitive appraisal (29.4%).Gaining insight into relational uncertainty provides youth with the means to acquire adaptive emotion regulation strategies